2020
DOI: 10.1002/bit.27560
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of 1,2,4‐butanetriol production from xylose in Saccharomyces cerevisiae by metabolic engineering of NADH/NADPH balance

Abstract: 1,2,4-Butanetriol (BT) is used as a precursor for the synthesis of various pharmaceuticals and the energetic plasticizer 1,2,4-butanetriol trinitrate. In Saccharomyces cerevisiae, BT is biosynthesized from xylose via heterologous four enzymatic reactions catalyzed by xylose dehydrogenase, xylonate dehydratase, 2-ketoacid decarboxylase, and alcohol dehydrogenase. We here aimed to improve the BT yield in S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…This avoids the detrimental effect of a large pH drop when producing BT from d -xylose ( Bañares et al, 2019 ). Compared with the recent reports on the biosynthesis of BT from d -xylose, the BT titer and yield produced from d -arabinose are not high enough ( Jing et al, 2018 ; Yukawa et al, 2021 ). There are still many aspects that need to be improved to further improve the production of BT from d -arabinose: screening for more active dehydrogenases and dehydratases, fine-tuning the expression levels of each enzyme, and balancing the ratio of NAD(P) + /NAD(P)H.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…This avoids the detrimental effect of a large pH drop when producing BT from d -xylose ( Bañares et al, 2019 ). Compared with the recent reports on the biosynthesis of BT from d -xylose, the BT titer and yield produced from d -arabinose are not high enough ( Jing et al, 2018 ; Yukawa et al, 2021 ). There are still many aspects that need to be improved to further improve the production of BT from d -arabinose: screening for more active dehydrogenases and dehydratases, fine-tuning the expression levels of each enzyme, and balancing the ratio of NAD(P) + /NAD(P)H.…”
Section: Resultsmentioning
confidence: 58%
“…d -Arabinose, the derivative of d -glucose, was used here to develop an alternative way to produce BT from d -glucose ( Figure 1B ). In previous studies ( Liu et al, 2012 ; Valdehuesa et al, 2014 ; Lu et al, 2016 ; Sun et al, 2016 ; Bamba et al, 2019 ), BT was mainly obtained from d -xylose through a four-step catalytic reaction: dehydrogenation, dehydration, decarboxylation, and reduction ( Wang et al, 2018 ; Bamba et al, 2019 ; Gao et al, 2019 ; Zhao et al, 2019 ; Yukawa et al, 2021 ). As the structure of d -arabinose is similar with d -xylose, a four-step synthetic pathway consisted of d -arabinose dehydrogenase, d -arabinonate dehydratase, 2-keto acid decarboxylase, and aldehyde reductase was accordingly conducted here to produce BT from d -arabinose ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Λοω ιντενσιτψ εξπρεσσιον οφ ΠΟΣ5 φρομ Σ. ςερε ισιαεβαλανςες τηε ΝΑΔΠΗ/ΝΑΔΗ ρατιο ανδ τηυς προμοτινγ α-φαρνεσενε βιοσψντηεσις ιν Π. pastoris It is well known that the intracellular NADH level is higher than the intracellular NADPH level. [39][40][41] Previous research indicated that heterologous expression of NADH kinase POS5 provides another source of NADPH except for the oxiPPP in yeast. 11,28 To further promote the α-farnesene production by optimizing the NADPH supply, we introduced the cPOS5 targeting in the cytosol from S. cerevisiae in strain X33-31.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, while increasing the supply of NADPH, systematic metabolic engineering is necessary for the construction of L-methionine engineered strains. In addition, NADPH imbalance sometimes affects product synthesis [ 28 ], rational control of NADPH levels may help to increase L-methionine synthesis.…”
Section: Discussionmentioning
confidence: 99%